If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = -6x + 11 Reorder the terms: 8x = 11 + -6x Solving 8x = 11 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 8x + 6x = 11 + -6x + 6x Combine like terms: 8x + 6x = 14x 14x = 11 + -6x + 6x Combine like terms: -6x + 6x = 0 14x = 11 + 0 14x = 11 Divide each side by '14'. x = 0.7857142857 Simplifying x = 0.7857142857
| 6+0.5x=0.5 | | 4(x-5)=29-3x | | 3x-1=107-9x | | 8p-4d-6d-8=32 | | (2x-5)(-x-1)=(-x-1)(x+8) | | 12(y+1)=24 | | 8(x-1)=8x+4-2x | | 5(m-12)=540 | | 5(y-2)=-5 | | 3x^4+6x^2=15x^3 | | 4(7+2)=24 | | 12+6-8x=-24 | | 9(y-1)=27 | | y=1/6-1/2 | | 2.88+0.21x=0.27(x+16) | | 7(y+4)=35 | | y^4+2y^3-y^2-16y+3=0 | | 2x+3y+3z=13 | | 2(3y+5)=28 | | k=1.2 | | f(x)=2k^2-4k(x)+1 | | z^4+2z^2-35=0 | | X+y-6z=-23.5 | | 7x+4=x+20 | | M=n+p | | 5x+8y+7=0 | | 0.25x+0.05(150-x)=26.70 | | 4=3(x+8)-7x | | X+(x+5)+(x*3)=60 | | 9x-4=29 | | 4x+y+2z=10 | | 7y-5=4y+3 |